A Comparison Between the GPI and PID Controllers for the Stabilization of a DC-DC "Buck" Converter: A Field Programmable Gate Array Implementation - Zurita-Bustamante, E. W.; Linares-Flores, J.; Guzman-Ramirez, E.; Sira-Ramirez, H. (IEEE transactions on industrial electronics (1982), 2011)
This paper presents a comparison between two stabilizing average output feedback controllers implemented on a field programmable gate array (FPGA) facility. A generalized proportional integral (GPI) controller and a proportional integral derivative (PID) controller are implemented using an FPGA, and their respective performances are duly compared. The GPI controller is found to present a better dynamic response than the PID controller in terms of the settling time while exhibiting a greater degree of robustness regarding disturbance rejection represented by severe changes in static and dynamic loads. The average controllers and their corresponding pulsewidth modulation actuators are implemented using a Spartan 3E1600 FPGA.